PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) UNTUK MENINGKATKAN KREATIVITAS ANAK USIA DINI DI KELAS TK B SEKOLAH KB-TK DAPENA SURABAYA - rafka, noviantinus; Arif, Muchamad (Universitas Narotama, 2024)
This research aims to increase creativity in early childhood with project learning. The method used in this research is qualitative research using interview and documentation methods. This research aims to describe the application of the project based learning method and student creativity after participating in project based learning. This research was carried out at the Dapena KB-TK school, Surabaya and the subjects of this research were the Class Teacher and Kindergarten B class students. The results of this research were that the teacher designed learning activities using the project based learning method through playing, telling stories and discussing activities according to predetermined themes. determined, and the learning support media uses loose parts so that students are enthusiastic about learning. The influence of project based learning on student creativity includes students not getting bored easily, being interested in creative activities, having high curiosity, self-confidence, daring to take risks, being open to new things, being imaginative, tolerant, and having responsibility. Keywords: Early childhood, Project based learning, creativity